DESCRIBING MATHEMATICS QUESTIONS IN ASSESSMENTS FOR THE VISUALLY IMPAIRED - Marcone, Renato; Bortolucci, Rodrigo [UNESP] (Universidade Federal de Sao Paulo, 2024)
This work is a continuation of the previous research presented in MES 11 (Marcone & Bortolucci, 2021), where we were trying to understand the role of the ledor (reader), a person who reads the test to the visually impaired person during an assessment. The work carried since then and up to the second half of 2022, following the conclusions made in our previous work, was focused on the study, understanding and systematisation of the process of adapting items, those related to mathematics such as drawings, tables, graphs, statements, and everything related to the elaboration of mathematics questions, and the activity of the maths test ledor. For this purpose, interviews were carried out with three professionals directly linked to this type of activity, with extensive experience in the activity of adapting mathematical tests, in addition to the analysis of theoretical references on the subject. We will present the main points addressed in each interview, such as the need for the test adaptation process to occur simultaneously with the test construction, so that the necessary interventions can occur before the test assembly is completed, followed by a discussion, with conclusions showing how important it is to describe an image properly, with minimum information, so the candidate can achieve the test with the time they have. This research was evaluated by an independent ethics committee and authorised to be carried out.
DESCRIBIR PREGUNTAS DE MATEMÁTICAS EN EVALUACIONES PARA PERSONAS CON DISCAPACIDAD VISUAL
DESCREVENDO QUESTÕES DE MATEMÁTICA EM AVALIAÇÕES PARA PESSOAS COM DEFICIÊNCIA VISUAL
Keywords: adaptation of teaching materials; inclusive assessment; inclusive mathematical education